Üst Gelir Grubu Konut Tercihleri Ve Mekan Kullanımları Üzerine Bir Araştırma - Sadıkoğlu, Hatice (Fen Bilimleri Enstitüsü, 2010)
Bu çalışma, 1980’lerden günümüze değişen üst gelir grubu konut tercihleri ve mekan kullanımlarını incelemeyi hedeflemiştir. Konut, tüketim ve toplumsal değişimler bağlamında ele alınmış süreç içerisinde konut ve donatı değişimleri incelenmiştir. Üst gelir grubu profili tariflenmeye çalışılmış ve bu grubun konutlarına yaklaşımları araştırılmıştır. ‘Residence’ örneği üzerinden yapılan bu çalışmada anket, kullanıcı ve tasarımcı görüşmeleri ve gözlemler sonucu belgeleme yapılmıştır. Değişen konut biçimlerini anlamak için kullanıcı profili ile beraber değerlendirilen üst gelir grubu konutları yeni mekanlarla ve kullanım ihtiyaçları ile beraber değişmiştir.

In this study using the gateaux differential new functional are obtained for linear elastic straight and circular bars on elastic foundation using functional analysis method. The functional also contains both the geometric and the dynamic boundary conditions. This new formulation is valid for the beam whether it is based on elastic foundation or not. Applying the variational methods to this functional and using linear shape function finite element matrix for straight and circular beams on elastic foundation are obtained in an explicit form. For straight bars it has two degrees of freedom per node and for circular bars it has six degrees of freedom per node. In this finite element formulation also variable bending rigity is considered. The comparison of the results with the exampes given in the literature was in a good agreement.
A Study On Housing Preferences And Space Use Of High Income Groups
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2010
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2010
Keywords: Residence; üst gelir grubu; konut; tüketim; high income groups; residential areas